Role of Udaka in the Pathogenesis and Management of Sthaulya (Obesity): Integrative Ayurvedic Perspectives with Anatomical correlation – A Narrative Review - Dr Hrutvij Kishor kharate,; Dr. Shelar Suvarna,; Dr. Umesh Tekawade,; Dr. Rokade Bharat,; Dr Darshana Ganesh Gadekar, (The Bioscan, 2026)
Sthaulya is a Santarpanottha Vikara marked by increased Meda buildup, limited movement, decreased vitality, and a higher risk of metabolic issues. The Charaka Samhita and other fundamental writings highlight the significance of Kapha, Meda, Agnimandya, and Srotorodha in the etiology of the disease. Nonetheless, in current integrated discourse, the contribution of Udaka—the physiological fluid principle that causes Kleda (moisture) and tissue hydration—continues to be understudied. This narrative review aims to link traditional Ayurvedic descriptions with anatomical, physiological, and metabolic data in order to evaluate the function of Udaka in the pathogenesis and treatment of Sthaulya. Primary Ayurvedic sources like the Charaka Samhita, Sushruta Samhita, and Ashtanga Hridaya were used in a narrative integrative review. The pertinent references to Udaka, Kleda, Kapha, Meda, and Sthaulya were methodically taken out and put together thematically. In a similar vein, contemporary biomedical literature was obtained from PubMed, Scopus, and Google Scholar using various keyword combinations, such as obesity, extracellular fluid, lymphatic dysfunction, adipose tissue inflammation, and extracellular matrix expansion. The anatomical and metabolic links between Udaka-mediated mechanisms were identified via conceptual mapping. According to traditional analysis, Udaka promotes physiological tissue lubrication, Dhatu nourishment, and Kapha stability. In particular, when combined with Agnimandya and Santarpana Ahara, the excessive rise of Udaka is pathological, leading to Kleda buildup and increasing the likelihood of Meda vriddhi, which eventually causes Srotorodha and Sthaulya. The reconstructed Samprapti shows a sequential cascade: Agnimandya → Ama formation → Kapha vriddhi → Udaka vriddhi → Kleda accumulation → Meda expansion → Srotorodha. Ayurvedic therapeutic approaches such as Langhana, Rukshana, Udvartana, and Lekhana- oriented treatments may have clinical advantages, at least in part, by altering tissue fluid dynamics and metabolic activation. Udaka is a viable conceptual counterpart to obesity-related extracellular fluid control and fluid-mediated metabolic dysfunction. Including this viewpoint broadens the knowledge of Sthaulya beyond adiposity and offers a translational framework for future empirical investigations of fluid biomarkers, body composition metrics, and lymphatic function in obesity phenotypes. To support this integrative model, thorough clinical validation is necessary.